Knowledge, attitudes and practices of sex professionals about prevention of sexually transmitted infections, before and after an educational intervention (Research, Society and Development, 2021)
This study aimed to assess knowledge, attitudes and practices of female sex workers about prevention of sexually transmitted infections (STIs), before and after an educational intervention. Descriptive, cross-sectional, intervention-type study with a quantitative approach, carried out with 75 female sex workers who worked in private environments in the city of Sobral - CE. A form was used with sociodemographic variables and knowledge, attitude and practice on Sexually Transmitted Infections (CAP survey). Data collection took place in April and May 2016, with the interviews being transcribed, analyzed and classified by knowledge, attitude and practices, before and after the educational intervention. The results showed that women have adequate knowledge about how to prevent STIs, recognizing that the male condom is one of the safest methods to avoid STIs/HIV. However, their attitudes and practices are dissonant when accepting to carry out programs without condoms for a higher price and not using them with fixed partners and preferential clients. After the intervention, an increase in knowledge about sexual health was detected. It was concluded that the financial factor in the sex trade supersedes knowledge, leading women not to assume proper attitudes and practices, which are obstacles to be considered in promoting the sexual health of the studied public.